The role of epigenetic factors in the pathogenesis of neurofibromatosis type 1 - R. N. Mustafin; E. K. Khusnutdinova (Успехи молекулярной онкологии)
The article describes the role of epigenetic processes in the tumorigenesis of neurofibromatosis type 1. The clinical manifestations of neurofibromatosis type 1 is characterized by a pronounced polymorphism erased from with single neurofibromas to severe forms with thousands  of tumors and complications even in patients with the same mutations. More than 1400 mutations in the NF1 gene have been reported, but have not yet identified genotype-phenotype correlations. Detected in the majority of neurofibromas mutation of the second allele of the gene NF1 and loss of heterozygosity may result from common disorders of genome stability and cell cycle regulation. Chance of tissue-specific  inactivation of the second allele is extremely low and can not prove the detection of neurofibromas in most patients with neurofibromatosis type 1. At the same time, the role of epigenetic factors for blocking of oncosupressors has been proven and can be applied to the development  of malignant tumors and neurofibromas. This assumption is proved by the fact that the majority of neurofibromas are formed in puberty, while inheriting the disease from mother to clinical manifestations more severe. This review presents the research on the role of miRNAs and specific methylation in the promoter region of NF1 tumorogenesis in neurofibromatosis type 1. Mutations in the NF1 gene are of great importance in the development of many malignancies. Due to the possibility of pharmacological correction of activity of microRNAs using antisense sequences, the study of epigenetic processes in neurofibromatosis type 1 promising to diagnose and treat not only the disease but also sporadic malignancies.